2017
DOI: 10.1108/ijlma-03-2016-0034
|View full text |Cite
|
Sign up to set email alerts
|

Accounting development in a changing environment: the case of Tunisia

Abstract: Purpose The purpose of this paper is to discuss accounting development in Tunisia, which is a developing North African country little known in the international accounting literature. Design/methodology/approach Methodologically, this paper is based on an exploratory approach. It uses the descriptive tradition of research by collecting and analyzing numerical and narrative data to identify and describe environmental factors that favor or hamper accounting development in Tunisia. Findings This paper indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Arguments for this practice are well documented. Ben Slama and Klibi (2017) argue that Tunisian GAAPs are incomplete and not updated compared to IFRS. This unachieved harmonization has pushed many listed companies to partly comply with some IFRS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arguments for this practice are well documented. Ben Slama and Klibi (2017) argue that Tunisian GAAPs are incomplete and not updated compared to IFRS. This unachieved harmonization has pushed many listed companies to partly comply with some IFRS.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon was qualified by Klibi (2016) as an unachieved harmonization with the IAS. In this context, Ben Slama and Klibi (2017), on the basis of a content analysis of the annual reports of Tunisian listed companies, indicate that these entities cannot reliably recognize accounting aspects of some of their activities. Among these activities, we cite deferred taxes, employee benefits, financial instruments, non-current assets held for sale and discontinued operations.…”
Section: Introductionmentioning
confidence: 99%
“…Zeghal et al (2012) found that firms in countries where the distance between pre-existing national GAAP and IFRS exhibit an improvement in accounting quality between pre- and post-adoption periods. With regard to the MENA region, apart from Saudi Arabia, Tunisia and Egypt (Hassan, 2008; Pacter, 2016; Slama and Klibi, 2017; Nurunnabi, 2018), most MENA countries did not have local accounting standards of their own (Kossentini and Othman, 2014; PwC, 2015; IASplus, 2016; IFRS Foundation, 2016; Pacter, 2016). Interestingly, those three countries are also non-IFRS adopters up to the time period of this study [8] (2006–2015).…”
Section: Reflection and Conclusionmentioning
confidence: 99%
“…In 1968, the National standard-setter set up the first domestic accounting system [plan comptable général (PCG)]. The PCG, very similar in spirit to the French General Accounting Plan, was “based on tax laws and promoted the publication of macro-economic indicators to satisfy the informational needs of the central government” (Ben Slama and Klibi, 2017, p. 761). In the mid-1980s, Tunisia suffered from an economic crisis.…”
Section: Theoretical and Regulatory Backgroundmentioning
confidence: 99%